Comparison of Lagrange’s and Newton’s interpolating polynomials - Srivastava, R B; Srivastava, Purushottam Kumar (Journal of Experimental Sciences, 2012)
A set of fourteen functions have been considered in various intervals. Lagrange’s and Newton’s interpolating polynomials have been obtained for each function using a computer program developed in C++ programming language. Average of the maximum percentage error for the functions in Newton’s interpolating polynomial and Lagrange’s interpolating polynomial are 765.3107 and 898.9139 respectively. This indicates that the Newton’s interpolating polynomial is approximately 1.174574 times better than the Lagrange’s interpolating polynomial.